Two stages of uniform delivered pricing and a monopolistic network in competitive electricity markets - Markus Ksoll (European Regional Science Association (ERSA), 2001)
In this contribution we assess the impact of spatial and non-spatial pricing techniques on market outcomes in deregulated electricity supply. Our analytical framework is a combination of the theory of spatial pricing and the theory of vertically related markets. A model of the traditional regional monopolies with vertical integration serves as a point of reference. The deregulated setting is characterized by a monopolistic transmission-network (upstream) and competitive production (downstream). The monoplistic network remains vertically integrated to one of the competitive producers, and serves at the same time as an essential input-facility to all producers, including the downstream-newcomers. The treatment of transport as a distinct market stage with endogenously determinded transmission- or access-rates sets this study apart from common analysis on spatial oligopolies. Specifically, we design two microeconomic models to compare two alternative pricing-arrangements: Uniform delivered pricing downstream and spatial pricing upstream on the one hand versus uniform delivered pricing downstream as well as upstream on the other hand. These options are both being practiced in different countries after deregulation and are subject to an ongoing political debate with little reference being made to theoretical foundations. The findings are threefold: Firstly, the strategic pricing behaviour on both, the monopolistic and the competitive stage is made visible. We show that in either arrangements there is no incentive on the side of the unregulated network-monopolist for complete vertical foreclosure, i.e. to set the network prices in such a way that all competition is excluded from his traditional market area. Secondly, we find that the preferences of consumers and of both types of firms vis-a-vis the spatial or non-spatial pricing policies deviate from those intuitively assumed by a number of authors. Thirdly, and most importantly, it can be shown that the total neglect of spatial components in network-pricing is accompanied by short run-welfare losses. Thus, if the simplification of network-pricing schemes by the abolishment of location- or distance-specific components induces intensified competition and - as the popular argument goes - enhanced productivity in suit, these gains will have to be weighed against the negative welfare effects caused by the disregard of spatial aspects. Too little attention is being paid to the latter side of the named trade-off.
Keywords: 330